Portretul primului arhiepiscop al nou reînființatei arhiepiscopii a Sucevei și Rădăuților: IPS Pimen Zainea în perioada 1991-2020 - Țanef, Constantin (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
This article, comes as a necessity, in order not to forget the person of the worthy of mention Pimen the Archbishop passed to the eternal ones on May 20, 2020. His life full simplity, zeal and faith, is a light and a blessing for those of us who knew him and had the opportunity to stand by him, to hear him, to guide us, to forgive us and to free us from sorry. That is why we are forced to pray for his soul, but to keep his memory alive and to make his life and activity known to him. A true Romanian and Orthodox, a true monk and priest, a true hierarch and patriot. Many have known him personally, but also from services and the media, each in his own way and we must come with our feelings and our feelings to discover it to those now and to those who will come after us. May his remembrance be eternal from generation to generation.